Preservation of Tomatoes in a Brick-Walled Evaporative Cooler - Babarinsa, Folorunso Adekunle; Omodara, Michael Ayodele (Journal of Postharvest Technology, 2016)
A double-walled evaporative cooler built of bricks with the interspaces filled with wet riverbed sand was tested for storage of tomato fruits (non-wrapped and wrapped in perforated and imperforated polyethylene bags). The temperature in the storage chamber was at 16-19 °C and 83-96% RH as compared to the ambient at 20-36oC and 34-70% RH. The evaporative cooler performed better than the ambient by reducing mean weight loss and decay in fruits by 53.7 and 41.2%, respectively. The shelf life of unpackaged tomatoes was 13 days in evaporative cooler as compared to 5 days under ambient conditions. Fruits stored in cooler were rated higher in sensory quality than those in the ambient. Perforated PE bags significantly reduced weight loss and decay in the stored tomatoes, thereby increasing shelf life to 20 days in the evaporative cooler and 13 days under ambient conditions. Tomatoes sealed in imperforated polyethylene bags had shorter shelf life of 7 and 9 days, under ambient and evaporative cooler respectively. The increase in shelf life of tomatoes in the cooler was attributed to lower temperature and higher relative humidity (RH) in the storage chamber. The study demonstrated that shelf life of tomatoes can be extended by the use of evaporative cooler.